The Principles & Practices of Water Consumption According to Ayurveda- A Cross- Sectional Survey: Life Sciences - Fadanavis, Madhura; Sawarkar, Dr. Gaurav; Sawarkar, Dr. Punam (International Journal of Life Science and Pharma Research, 2023)
Well-balanced water (Pana) and food (Aahar) input are essential. Ayurvedic literature outlines certain rules for proper food intake and Ahar, retaining vigor and life duration. In water, trace elements can be found in high concentrations. Children, pregnant women, and the elderly have higher water requirements. Drinking water can be processed in a variety of ways using natural methods. The context of Ayurveda mentions the benefits of drinking Ushnodaka (warm water). In Ayurveda, there are various advantages of drinking water. The benefits of drinking warm water were also emphasized in Ayurveda. Drinking water habits are crucial for good health because dietary habits are important for a person’s lifestyle. The aim and objective of the study were to understand the domestic cause of lifestyle illnesses associated with improper water consumption habits and to create awareness regarding water consumption practices. Data was gathered from the general public who suffer from lifestyle diseases and those ready to participate. The data was collected with the specially designed inquiry form and a standard Prakriti (physical and mental constitution of the body) questionnaire. 250-sample size, among which 40% were male and 60% female. It was found that most of the population belongs to Kapha dominant Prakriti, i.e., 149 (59.6%), whereas 45 (18%) and 56 (22.4%) population was of Vata & Pitta dominant Prakriti, respectively. 80.4 % of people drink water in seating positions, and 56% directly swallow water. 70% of people drink normal water, and 44 % drink clay pot water in summer. Type II diabetes is the most common lifestyle disorder. A reduction in water intake triggers type II diabetes. It has been discovered that people do not immediately drink water after getting out of bed, which causes gradual weakness. Instead, people drink water before a meal, which helps them to lose weight. The intake of one glass of water before going to bed reduces Vata and Kapha and prevents indigestion.